Regulation of Endosomal Sorting and Maturation by ER-Endosome Contact Sites. (June 2022) - Jean, Steve; Nassari, Sonya
Endosomes are a heterogeneous population of intracellular organelles responsible for sorting, recycling, or transporting internalized materials for degradation. Endosomal sorting and maturation are controlled by a complex interplay of regulators, with RAB GTPases and phosphoinositides playing key roles. In this decade, another layer of regulation surfaced with the role played by membrane contact sites between the endoplasmic reticulum (ER) and endosomes. Specific regulators of ER-endosome contact sites or proteins localized at these sites are emerging as modulators of this complex endosomal ballet. In particular, lipid transfer or recruitment of various complexes and enzymes at ER-endosome contact sites play an active role in endosome sorting, scission, and maturation. In this short review, we focus on studies describing ER-endosome contact sites in these three endosomal processes.